АДАПТАЦИЯ УЧЕБНЫХ МИГРАНТОВ, ОБУЧАЮЩИХСЯ В РОССИЙСКИХ ВУЗАХ ПУТЕМ ВЫЯВЛЕНИЯ РАЗЛИЧИЙ В КУЛЬТУРНЫХ КОДАХ - Черникова, А.А. (My University, 2019)
Аннотация В статье описаны процессы адаптации учебных мигрантов, обучающихся в российских вузах путем выявления различий в культурных кодах, приведены различные условия адаптации, описаны феномены культурных кодов. Abstract The article describes the processes of adaptation of educational migrants studying in Russian universities by identifying differences in cultural codes, presents various conditions for adaptation, describes the phenomena of cultural codes.
Adaptation of educational migrants training in russian universities by determining differences in cultural codes
Keywords: адаптация; культурный код; учебная миграция; adaptation; cultural code; educational migration